Significance of Classroom Management - Pradhan, Bibhuti Bhusan (International Journal of Psychosocial Rehabilitation, 2019)
Although focus has started to be given to bullying in schools, little is understood about the interaction between classroom management and classroom bullying. A study of findings and literature relating to discrimination in the school environment, classroom management, instructor discipline, and student actions will be the method to discuss this partnership. Evidence from a number of areas shows that several factors are working to create the environment where bullying is more possible. These comprises of methods of discriminatory and harsh discipline, lesser-quality classroom instruction, disorganized classroom and school settings, and antisocially characterized student social structures.A need for restoration and in-service instruction on classroom management activities and student abuse is demonstrated in potential directions. Future studies should also explore researching the connection between classroom management activities and student bullying, as well as further examining student bullying teacher and teacher bullying students.